Parametrically forced Geophysical Model and Strange Non Chaotic Attractor - Middya, Rajarshi; Chowdhury, Asesh Roy (Journal of Applied Nonlinear Dynamics, 2026)
A classical glacial climate model previously developed by Saltzman et al. [1–4] and Nicollis et al. [5] is analysed when parametric forcing is present. This particular model was actually used in the study of glacier formation. Our analysis mainly focusses on the issues due to the periodic or quasiperiodic variation of these parameters with time. It is observed that this quasiperiodically driven Saltzman model leads to the generation of Strange Nonchaotic Attractor (SNA), which is very interesting because it is neither a periodic state nor a fully chaotic one. Due to this fact, it is usually very difficult to pinpoint its existence and generation. In particular, we focus on an intermittency transitions of type I and on subharmonic bifurcation leading to type III intermittency. The properties of the attractor are characterised by the finite time Lyapunov exponents, its variance and their distributions along with Poincar´e sections. The zone of existence of SNA for different parameter values have been found.